Pengaruh Kinerja Guru Bersertifikasi terhadap Prestasi Belajar Siswa di MI Ma'had Islamy Kotagede Yogyakarta - Sumarsih (Jurnal Pendidikan Madrasah, 2020)
This research aims to analyze the influence of certified teacher performance on student learning achievement in MI Ma'had Islamy Kotagede Yogyakarta. This research is a field research (research feed) with a quantitative approach. The data collection method uses document questionnaires. The results showed that the performance of MI Ma'had Islamy certified teachers can be categorized very well, the learning achievement of MI Ma'had Islamy students is also in the good category, while the author's hypothesis is rejected. There is no significant influence between the performance of certified teachers on the learning achievement of students in MI Ma'had Islamy. The government certification program has an impact on the performance of MI ma'had Islamy teachers but has no effect on students' learning achievement.